African cinemas : decolonizing the gaze - Barlet, Olivier (Zed Books ; Distributed in the USA exclusively by St. Martin's Press, Inc, 2000)
This book is both a personal journey and an introduction to the cinema cultures of Africa. A book about the politics of cultural survival, it is also a major overview of African cinema and television.